An analysis of residue net estate distribution to bayt al-māl in Singapore. Issue 1 (30th March 2020) - Rasban, Sadali; Abdullah, Adam; Hasan, Aznan
Abstract : Purpose: This paper aims to examine the current practice in Singapore regarding an inheritance issue: disposal of the residual net estate to the bayt al-māl, which is identified as the Islamic Religious Council of Singapore (Majlis Ugama Islam Singapura, MUIS). The issue arises when the deceased leaves farḍ (fixed-share) heir(s) and/or dhawū al-arḥām (outer family members) but there is no ʿaṣabah (agnatic residuary heir by blood). Farḍ legal heirs are those beneficiaries for whom the Qurʾān prescribes inheritance of a pre-determined share. Disposal of the residual net estate to the bayt al-māl results in a reduction in the share due to the farḍ legal heir or worse, a total loss to the dhawū al-arḥām legal heirs. Design/methodology/approach: A qualitative approach based on library and case study research has been adopted to elaborate practices that fall under the purview of the Administration of Muslim Law Acts (AMLA), Chapter 3. Findings: The current practice seems biased against, especially, women and spouses. It creates high dissatisfaction in the community, especially those affected by such practices. This paper elaborates on the practice of residual net estate distribution in Singapore and the contemporary practices of the four Sunni madh-habs – the Ḥanafī, Mālikī, Shāfiʿī and Ḥanbalī jurisprudential schools – in other countries. Research limitations/implications: In Singapore, Muslim law is defined and implemented by the civil court, not the Syariah Court or MUIS. The recommendation to change from the current classical practice by the Syariah Court and MUIS to the contemporary practice that is relevant to today's context lies with the civil court and Government of Singapore. The choice for the Syariah Court and MUIS to adopt the contemporary practice as per Ḥanafī School by rule of the court or the government is beyond this research. Zayd ibn Thābit, Caliph Abū Bakr and a small number of companions held the view that the residue net estate asset must go to the bayt al-māl, the current classical practice. The contemporary practice adopted by Sayyidina ʿUthmān ibn ʿAffān, Jābir ibn Zayd and majority of the companions' view, is not in favour of the residue net estate asset to go to the bayt al-māl ; rather they view that it must be returned to the legal heirs. Practical implications: Awareness in the community in the current controversial practice in Singapore when the residue net estate through the farāʾiḍ law was giving to bayt al-māl instead of returning to farḍ or dhawū al-arḥām in the absence of the ʿaṣabah legal heir as stated in the Inheritance Certificate issued by Syariah Court. Social implications: To understand the contemporary Muslim law and the practical and just application in today's Singapore context as supported by the AMLA, Chapter 3. Originality/value: This is the first study that challenges the current practice by the Syariah Court and MUIS in Singapore, thereby endeavouring to restore justice to the community.